Sinergitas Pembangunan Tata Ruang Pertahanan Daerah dalam Menghadapi Ancaman Non-Militer di Indonesia - Alfajri Alfajri; Azhari Setiawan; Herry Wahyudi (Global Strategis, 2019)
This article aims to understand and explain the local context of state’s defense toward non-military threats in Indonesia. As the broading and deepening development of security significance, non-traditional security agenda urges multi-levels and multi-sectors synergy especially in the local government because the nature of non-military threats in Indonesia developed at the local level. First, authors review numbers of literatures about non-traditional security, non-military threats and the securitization theory. Second, the article elaborates the strategic environment—global, regional, and national—and threats perception from the perspective of Indonesia’s defense posture. After that, the article explains securitization aspects of multi-level and multi-sectors synergy on facing the non-military threats at the local level. The result of this research is the synergy of national development, regional development and national defense development needs to be synchronized with the support of clear regulations, considering the available resources to achieve real community welfare, both in terms of income, employment opportunities, business opportunities, access to policy making, competitiveness, and an increase in the human development index. The strategic relations between stakeholders in the synergy of national defense development is essential to achieve formidable defense. Policy socialization between vertical agencies of ministries/institutions and regional governments needs to be optimized and intensified so that there will be a common perception in the management and implementation of national defense development on dealing with non-military threats.